Protective effect of nerolidol on lipopolysaccharide-induced acute lung injury through the inhibition of NF-κB activation by the reduction of p38 MAPK and JNK phosphorylation. (June 2020) - Chen, Shih-Pin; Su, Chun-Hung; Huang-Liu, Rosa; Lee, Min-Wei; Chiang, Chen-Yu; Chen, Wen-Ying; Chen, Chun-Jung; Wu, Sheng-Wen; Kuan, Yu-Hsiang
Graphical abstract: Highlights: Nerolidol suppressed proinflammatory responses in LPS-induced ALI mice. Nerolidol inhibited phosphorylation of NFκB p65 in LPS-treated mice. Nerolidol inhibited phosphorylation of p38 MAPK, JNK, ERK in LPS-treated mice. Inhibition of NF-κB p65, p38 MAPK and JNK was similar to anti-inflammation. Nrolidol acting as a protective reagent in LPS-induced ALI mice. Abstract: Acute lung injury (ALI) is a severe syndrome, and there are no effective therapeutic appropriate medicines. Nerolidol, which exists in the essential oils of aromatic plants and flowers, exhibits antioxidative and anti-inflammatory activities. The present study evaluated the potential protective effect of nerolidol in ALI and the related mechanism in lipopolysaccharide (LPS)-treated mice. Here, nerolidol inhibited the LPS-induced neutrophil and other leukocyte infiltration of the alveolar space. LPS increased cytokines, chemokines, and adhesion molecules, and proinflammatory protein production was inhibited by nerolidol. LPS-induced phosphorylation of NF-κB p65, p38 MAPK, JNK, ERK were inhibited by nerolidol. The inhibitory concentration of nerolidol for the phosphorylation of NF-κB p65 and its upstream factors, p38 MAPK and JNK, was similar to the inflammatory responses of ALI. In conclusion, nerolidol is a potential protective agent in ALI via the inhibition of NF-κB activation and its upstream factors phosphorylation of p38 MAPK and JNK.